Translation and validation of the Karitane Parenting Confidence Scale in Nepali language. (May 2016) - Shrestha, Sharmila; Adachi, Kumiko; Shrestha, Sarita
Abstract: Background: a mother׳s lack of confidence in the early postnatal period may negatively influence their ability to care for their infant. Parenting confidence contributes to the parent-infant relationship and other aspects of infant development. The Karitane Parenting Confidence Scale is a 15-item self-report questionnaire designed to measure parents' subjective confidence in their parenting abilities, or 'perceived parenting self-efficacy', and is designed for mothers with infants aged 0–12 months. Objectives: to translate the Karitane Parenting Confidence Scale into Nepali language and assess the validity and reliability among Nepalese postnatal mothers. Design: cross-sectional study. Setting: outpatient department of maternity and women׳s hospital in Kathmandu, Nepal. Participants: one hundred postnatal mothers within 5–6 weeks of childbirth were recruited using the convenience sampling method. Methods: following back-translation procedures, mothers completed questionnaires during follow-up visit at immunisation/postnatal clinics. For the validity and reliability have been assessed internal consistency, discriminant validity, and construct validity. Results: the translated Karitane Parenting Confidence Scale mean score was 35.47±5.48, ranging from 32 to 42. Cronbach׳s alpha coefficient for internal consistency was 0.87. A difference was found between primiparous and multiparous mothers׳ confidence scores. There was a significant correlation between maternal confidence and anxiety scores. Demographic response patterns suggest that the maternal confidence level was affected by education level. Conclusions: the Nepali version of Karitane Parenting Confidence Scale showed adequate reliability and validity. Therefore, the Nepali Karitane Parenting Confidence Scale is considered a suitable instrument to assess maternal confidence in Nepali postnatal mothers. Highlights: Maternal self-efficacy is an important variable for infant nurturing and development The translated version of KPCS may be valid and reliable measure among Nepalese mothers. Maternal confidence level was affected by education level. There was significant difference in maternal confidence between multiparous and primiparous.